Timing of paraglacial rock‐slope failures and denudation signatures in the Cantabrian Mountains (North Iberian Peninsula). (31st May 2018) - Rodríguez‐Rodríguez, Laura; González‐Lemos, Saúl; Ballesteros, Daniel; Valenzuela, Pablo; Domínguez‐Cuesta, María José; Llana‐Fúnez, Sergio; Jiménez‐Sánchez, Montserrat
Abstract: Glacial erosion of hillslopes and stress changes induced by the transition from glacial to nonglacial conditions exert a strong influence on slope instability and are considered among the scope of paraglacial geomorphology. Failure mechanisms and coupling between paraglacial rock‐slope failures (RSFs) and fluvial erosion are difficult to define. Here we show a preliminary spatio‐temporal framework of paraglacial RSFs in a small catchment of the central Cantabrian Mountains, the San Isidro valley, with a dense concentration of RSFs. Preliminary radiocarbon dates obtained from two floodplain sequences deposited upstream from RSFs indicate that their sedimentation started as consequence of valley impoundment by RSFs after glacier retreat (after approximately 16.1 ka), consistent with the deglaciation pattern of nearby valleys. RSFs continued during the Holocene. Glacier erosion, debuttressing, and stress‐release conditions played an important role in slope destabilization as preparatory factors in all cases and probably triggered the oldest events. However, the long prefailure endurance (approximately 12 ka) between RSFs points to other factors such as rainfall and fluvial down‐cutting of hillslopes as triggers for Holocene events. Postglacial fluvial incision rates of 2.2–2.5 mm a −1 were estimated along gullies carved into bedrock areas nonaffected by RSFs. These values are one order of magnitude higher than previous rates based on other geomorphological proxies (~ 0.2 mm a −1 ), suggesting accelerated fluvial incision following the last deglaciation. Local RSFs contributed to increase in fluvial incision rates by a factor of three. This study provides a quantitative perspective of postglacial land degradation relevant for understanding postorogenic landscape evolution.